Dominant tolerance: activation thresholds for peripheral generation of regulatory T cells. - Graca, L; Chen, T; Le Moine, A; Cobbold, S; Howie, D; Waldmann, H (2005)
In recent years, regulatory T (Treg) cells have reached centre-stage in immune tolerance research. A role for Treg cells in preventing autoimmunity or generating transplantation tolerance is now undisputed. However, in spite of a surge in publications dedicated to Treg cells, surprisingly little is known about their induction, biology and mechanisms of action. In this Opinion, we discuss the facts and the controversies regarding their role in transplantation tolerance. We suggest that peripheral generation of Treg cells, crucial for the generation of dominant transplantation tolerance, might be a consequence of sustained suboptimal antigenic stimulation, and that transforming growth factor-β (TGF-β) might contribute to this process by increasing the threshold for T-cell activation. © 2004 Elsevier Ltd. All rights reserved.